Gender and environmental knowledge in natural resources management in Kisumu County, Kenya - Mogoria, Naomi A. (JOOUST, 2015)
Environmental knowledge acquired by local communities over time as they interact with the environment is a vital asset in environmental conservation. However, few studies have been conducted to examine the local knowledge endowment accrued from interactions between men and women as they get involved in environmental activities. The main objective of this paper was to determine the level of environmental knowledge for men and women towards the environment within Kisumu County. Out of a total of 16860 households, a survey of 376 households was carried out using simple random sampling. Data was collected using questionnaire survey and literature reviews. Descriptive methods of data analysis were used to analyze the data. The results of the paper showed that both men and women considered tree planting to have very positive impact on the environment, while drawing water from the lake was considered not to have any impact on the environment, but washing in the lake was considered to have a very negative impact on the environment. The findings on the local community knowledge on various environmental impacts of activities are of importance to policy makers and project implementers because they can use the information to carry out environmental awareness campaigns. In conclusion, local communities have environmental knowledge on level of impact activities have on the environment. This paper recommends up scaling of environmental knowledge for men and women through formulation of an appropriate framework for integration of gender perspective in environmental management activities. Also relevant institutional actors should involve local communities at all stages of projects for improved local community livelihoods.
1st JOOUST Scientific Conference
Keywords: Gender; Environmental knowledge; Local community; Natural resources; Environmental management